Characterization of piezoelectric materials for simultaneous strain and temperature sensing for ultra-low frequency applications. (15th July 2015) - Islam, Mohammad Nouroz; Seethaler, Rudolf; Alam, M Shahria
Abstract: Piezoelectric materials are used extensively in a number of sensing applications ranging from aerospace industries to medical diagnostics. Piezoelectric materials generate charge when they are subjected to strain. However, since measuring charge is difficult at low frequencies, traditional piezoelectric sensors are limited to dynamic applications. In this research an alternative technique is proposed to determine static strain that relies upon the measurement of piezoelectric capacitance and resistance using piezoelectric sensors. To demonstrate the validity of this approach, the capacitance and resistance of a piezoelectric patch sensor was characterized for a wide range of strain and temperature. The study shows that the piezoelectric capacitance is sensitive to both strain and temperature while the resistance is mostly dependent on the temperature variation. The findings can be implemented to obtain thermally compensated static strain from piezoelectric sensors, which does not require an additional temperature sensor.